Precarização do trabalho no setor de supermercados : um estudo de caso com trabalhadores em Natal - Gê, Pollyanna Carvalho de Siqueira (2006)
Precarization of work, process situated historically after the third Industrial Revolution, express itself as one of the faces of changes in production modus and working conditions. The present study aims to identify the process of work precarization in supermarket sector in Natal municipality. The choice for this sector and professional category is based on low investment in studies on the commercial sector and on technological and administrative transformations that supermarkets have implemented. After a bibliographical review, ten indicators of precarization were chosen which permitted to set up a schedule to interviews and its application to employees of two supermarkets (local companies) in Natal area. The following working functions were chosen to participate in the survey: cashier, display assistant (shelf-stacker) and attendants (N=6). From the interviews we developed an analysis of categorical contents in order to identify the presence of precarization indicators. Categorizations allowed us to identify five major themes: work categorization; work meaning: its attributes; work meaning: work centrality; comments on the employment of apprentices or trainees; and transversal work contents. Such themes contents express or not the presence of precarization process at supermarket sector in Natal area. Precarious work is identified in participants speech when they refer to the employees decreasing power in salaries negotiation between them and employers that institute the precarious work conditions